Cps1-Compliant Economic Dispatch for a Single Balancing Authority System - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2016)
The integration of variable generation to power systems has led to a revision of ancillary service definitions. In the case of secondary frequency control, these concerns are related with the dimensioning of reserves to cope with variability and uncertainty, and, ultimately, with the compliance with performance standards. One of such a performance standards used in North America is the Control Performance Standard 1 (CPS1), that measures the contribution of a balancing authority to frequency control within an interconnection. This paper proposes an Economic Dispatch formulation that ensures CPS1 compliance in the case of a single balancing authority. The formulation assumes that the ramping capability of units and generation variability and uncertainty are given, and determines the optimal procurement of secondary reserves to comply with CPS1. An explanatory example will be presented. © 2015 IEEE.